2014
DOI: 10.1186/1471-2407-14-443
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a regulates glucose metabolism by direct targeting PDHX in colorectal cancer cells

Abstract: BackgroundReprogramming energy metabolism has been an emerging hallmark of cancer cells. MicroRNAs play important roles in glucose metabolism.MethodsThe targets of microRNA-26a (miR-26a) were predicted by bioinformatics tools. The efficacy of miR-26a binding the 3′-untranslated region (UTR) of pyruvate dehydrogenase protein X component (PDHX) mRNA was evaluated using a dual-luciferase reporter assay. The PDHX expression at the mRNA and protein level in several colon cancer cell lines was quantified with real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 42 publications
(53 reference statements)
0
75
0
1
Order By: Relevance
“…This apparent discrepancy renders miRNA regulation even more astonishing, as it suggests that a given miRNAmRNA interaction is not oncogenic or tumor suppressing per se, but can have either outcome depending on the context. The evidence that we present here, together with the targeting of PDHX, 17 highlights the importance of this miRNA as an oncogenic regulator in CRC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This apparent discrepancy renders miRNA regulation even more astonishing, as it suggests that a given miRNAmRNA interaction is not oncogenic or tumor suppressing per se, but can have either outcome depending on the context. The evidence that we present here, together with the targeting of PDHX, 17 highlights the importance of this miRNA as an oncogenic regulator in CRC.…”
Section: Discussionmentioning
confidence: 88%
“…And this function, together with the previously observed regulation of glucose metabolism through PDHX targeting, 17 accentuates the importance of miR-26a as a multifunctional regulator in colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two different nucleotides between the mature sequences of miR-26a and miR-26b, whereas miR-26a-1 and miR-26a-2 have fully identical sequences arising from the 5’ arm of the respective precursors [40]. Plenty of publications reported that miR-26a plays an important role in various diseases [41-43], and most of them focused on cancer or cancer-related diseases, including colorectal, breast, ovarian, and gastric cancers [42, 44-47]. For example, miR-26a promotes cell proliferation and apoptosis by targeting phosphatase and tensin homolog ( PTEN ), Cyclin D1, and Bcl-2 in cancer cells [48-50].…”
Section: Mirna Biogenesis and Functionmentioning
confidence: 99%
“…One of the strategies that cancer cells use to achieve glycolytic switch is through controlling PDHX and PDK. It has been reported that miR-26a targets PDHX in colorectal cancer cells [ 98 ] and that miR-375 regulates cell survival by targeting PDK1 in gastric carcinomas [ 99 ]. Interestingly, another powerful microRNA, miR-34a, targets many glycolytic enzymes including HK1, HK2, LDHA and GPI, as well as PDK1 [ 100 , 101 ].…”
mentioning
confidence: 99%